Statin use and survival following a diagnosis of ovarian cancer: A prospective observational study. Issue 7 (20th October 2020) - Majidi, Azam; Na, Renhua; Jordan, Susan J.; De Fazio, Anna; Webb, Penelope M.; ,
Abstract: Most women with ovarian cancer have a poor prognosis, but studies have reported an association between statin use and improved survival. We investigated the potential survival benefit of statins in women with ovarian cancer using data from the Ovarian cancer Prognosis and Lifestyle study, a prospective study of Australian women aged 18 to 79 years, diagnosed with ovarian cancer from 2012 to 2015 and followed for 5 to 8 years. We obtained information from patient‐completed questionnaires and medical records. We defined exposure based on prediagnosis use, as most women used statins continuously (prediagnosis and postdiagnosis) and few started using statins postdiagnosis. We measured survival from date of first treatment (surgery or neoadjuvant chemotherapy) until date of death or last follow‐up. We used Cox regression to calculate hazard ratios (HR) and 95% confidence intervals (CI), adjusting for potential confounders. To reduce bias due to confounding by indication, we also applied inverse probability of treatment weighting (IPTW). Of 955 eligible women, 21% reported statin use before diagnosis. Statin users had a slightly better survival (HR = 0.90, 95% CI = 0.70‐1.15) that was driven by lipophilic statin use (HR = 0.82, 95% CI = 0.61‐1.11), with no association for hydrophilic statins (HR = 1.04, 95% CI = 0.72‐1.49). The IPTW model weighted to all women with ovarian cancer also suggested a possible reduction in mortality associated with lipophilic statins (HR = 0.80, 95% CI = 0.54‐1.21). In analyses restricted to women with hyperlipidaemia, the HRs were further from the null. Our findings are consistent with previous evidence, suggesting that lipophilic statins might improve ovarian cancer survival. Further investigation, in larger cohorts, or preferably in a randomised trial, is required. Abstract : What's new? Ovarian cancer generally has a poor prognosis. Some previous studies have indicated that statins may improve survival, but these may have been subject to various forms of bias. In the present study, the authors used statistical methods that minimize bias to analyze data from a prospective Australian trial. They found that lipophilic statins may indeed enhance survival for ovarian cancer patients, particularly for women with hyperlipidaemia. Hydrophilic statins had no effect on survival. Further investigations to evaluate lipophilic statins in larger cohorts, preferably randomized clinical trials, are recommended.